Financial literacy and household asset allocation: Evidence from micro‐data in China. Issue 4 (30th September 2021) - Lu, Xiaomeng; Xiao, Jingna; Wu, Yu
Abstract: Improving household asset allocation (HAA) ability can enable households to increase consumption and promote the steady growth of China's economy. However, HAA decisions in China are suboptimal. This may be related to households' limited financial literacy. Based on 2017 and 2019 China Household Finance Survey data, this study examines the role of financial literacy in improving HAA. It finds that the higher the household's financial literacy, the higher the household's score in the asset allocation evaluation because households with higher financial literacy pay greater attention to economic and financial news and are more inclined to seek advice from investment advisors. Further analysis shows that the optimization effect of financial literacy on HAA is greater in households that are wealthy, higher educated, and located in areas with better regional financial development. In conclusion, helping households improve their financial literacy is an important step toward improving HAA ability.